Health Related Quality of Life of Patients with Cardiovascular Disease attending Sahid Ganagalal National Heart Center, Janakpurdham, Province 2, Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Individuals' subjective perceptions of their own physical, mental, and social health and functioning make up what is known as "health-related quality of life" (HRQL). The alarming rise in cardiovascular diseases (CVDs) has received little national attention because Nepal’s health system places more of an emphasis on maternal, neonatal, and child health as well as communicable diseases. The study was conducted to assess the health related quality of life (HRQL) of patients with cardiovascular disease attending Sahid Gangalal National Heart Center, Janakpurdham, Madhesh Pradesh, Nepal.MATERIALS AND METHODS: A descriptive cross sectional study design was adopted for the study. This study was carried out in outpatient department (OPD) of Sahid Gangalal National Heart Center, Madhesh Pradesh, Janakpurdham, Nepal. The instrument used for the study was WHOQOL-BREF, which consists of 26 items.RESULTS: 70.4% of the respondents had a good quality of life, 80.8 % patients were dissatisfied with health, 63% of the respondents were with good physical health, 75% had stable psychological health, 67% had active social relationships and 56% were with inadequate environmental status.CONCLUSIONS: Despite a history of cardiovascular illnesses, majority of study participants reported a high quality of life. However, the assessment device employed in this study assessed overall quality of life.